Linear stability analysis for severe slugging in air–water systems considering different mitigation mechanisms. (July 2015) - Azevedo, G.R.; Baliño, J.L.; Burr, K.P.
Highlights: We study stability of the steady state of a dynamic model for severe slugging in air–water systems. We include separation pressure increase, choking and gas injection as mitigation devices. We build stability maps showing the influence of the mitigation devices. We compare the stability maps built with linear stability theory and numerical simulations, showing excellent agreement. We stress the necessity of including stability analysis based on the dynamic models in computer simulation codes. Abstract: This work presents a numerical study of the effects of mechanisms such as gas injection, choking and different boundary conditions on the stability of the stationary state for two-phase flows in vertical and catenary pipeline–riser systems. Numerical linear stability analysis is performed to a suitable mathematical model for the two-phase flows in a pipeline–riser system. The mathematical model considers the continuity equations for the liquid and gas phases and a simplified momentum equation for the mixture, neglecting inertia (NPW – no pressure wave model). A drift flux correlation, evaluated in local conditions, is utilized as a closure law. Gas injection and a choke valve are added, respectively, at the riser bottom and top. The extended model is applied to air–water pipeline–riser systems reported in the literature. Numerical linear stability analysis results are compared with experimental and numerical results reported in the literature with excellent agreement.